An Attempt to Improve Electrochemical Performances of Lignin‐Based Hard Carbon Microspheres Anodes in Sodium‐Ion Batteries by Using Hexamethylenetetramine. Issue 33 (3rd September 2018) - Yu, Xiaochen; Yu, Baojun; Zhang, Jie; Zhang, Yang; Zeng, Jingxuan; Chen, Mingming; Wang, Chengyang
Abstract: Lignin‐based hard carbon microspheres anodes were prepared and applied in sodium‐ion batteries (SIBs), which delivered a high initial coulombic efficiency (ICE) and good capacity. The precursors of lignin hard carbon microspheres are thermoset lignin microspheres. By reversed‐phase polymerization, different physicochemical properties of lignin microspheres were prepared by adjusting the amount of hexamethylenetetramine (HMTA). The influence of HMTA on microstructure, thermal stability and electro‐chemical properties were studied in detail. Fourier transform infrared (FT‐IR) spectroscopy, thermogravimetric, Brunner−Emmet−Teller (BET) measurements, X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS) and Raman analysis showed that more functional groups are introduced and HMTA improved the thermal stability and the carbon disorder. It is found that the most appropriate addition amount of HMTA is 5 wt % after comparison. The optimal sample exhibits the best electrochemical performance. The initial discharge/charge capacity of 494.4/393 mAg −1 (ICE of 79.6%) is achieved at a current density of 0.1 C (1 C=250 mAg −1 ), and after 250 cycles at 0.4 C, the capacity retention ratio is 90.3%. This high reversible capacity proves that adding an appropriate amount of HMTA is an effective strategy to improve the electrochemical performance of SIBs. Abstract : By reversed‐phase polymerization, different physicochemical properties of lignin microspheres were prepared by adjusting the amount of HMTA (hexamethylenetetramine). HMTA changes the degree of cross‐linking and thermal stability carbon microspheres. The sample has good electrochemical performance in SIBs (sodium‐ion batteries).